Pengaruh Ketimpangan Pendapatan Terhadap Kemiskinan Di Indonesia - Siti Ro’asih; Dinda Aulia Putri; Dwi Teguh Andika Prakoso; Syafaatul Hidayati (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of income inequality on poverty in Indonesia from a macroeconomic perspective through a qualitative literature review approach. Income inequality remains one of the major economic challenges in developing countries, including Indonesia, because unequal income distribution can widen social disparities, reduce access to education and health services, and increase the vulnerability of low-income groups. This research employs a qualitative descriptive method by reviewing scientific journals, government reports, and macroeconomic publications issued within the last five years. The analysis focuses on the relationship between income inequality, economic growth, unemployment, inflation, human development, and poverty levels in Indonesia. The findings indicate that high income inequality contributes significantly to the persistence of poverty, particularly in rural areas and regions with limited economic access. Although Indonesia has experienced economic growth in recent years, the benefits of growth have not been distributed evenly across society. The study also finds that inequality in access to education, employment opportunities, technology, and productive assets strengthens structural poverty. Therefore, policies aimed at equitable economic development, improving human capital, strengthening social protection, and expanding employment opportunities are essential to reduce poverty and maintain long-term economic stability.